Accelerated tissue regeneration in decellularized vascular grafts with a patterned pore structure. Issue 14 (17th November 2021) - Mahara, Atsushi; Kojima, Kentaro; Yamamoto, Masami; Hirano, Yoshiaki; Yamaoka, Tetsuji
Abstract : Tissue regeneration in decellularized vascular grafts was accelerated with a patterned pore structure. Abstract : Decellularized tissue is expected to be utilized as a regenerative scaffold. However, the migration of host cells into the central region of the decellularized tissues is minimal because the tissues are mainly formed with dense collagen and elastin fibers. This results in insufficient tissue regeneration. Herein, it is demonstrated that host cell migration can be accelerated by using decellularized tissue with a patterned pore structure. Patterned pores with inner diameters of 24.5 ± 0.4 μm were fabricated at 100, 250, and 500 μm intervals in the decellularized vascular grafts via laser ablation. The grafts were transplanted into rat subcutaneous tissue for 1, 2, and 4 weeks. All the microporous grafts underwent faster recellularization with macrophages and fibroblast cells than the non-porous control tissue. In the case of non-porous tissue, the cells infiltrated approximately 50% of the area four weeks after transplantation. However, almost the entire area was occupied by the cells after two weeks when the micropores were aligned at a distance of less than 250 μm. These results suggest that host cell infiltration depends on the micropore interval, and a distance shorter than 250 μm can accelerate cell migration into decellularized tissues.